2011
DOI: 10.1007/s12207-011-9102-7
|View full text |Cite
|
Sign up to set email alerts
|

Do Motivations for Malingering Matter? Symptoms of Malingered PTSD as a Function of Motivation and Trauma Type

Abstract: Psychological disorders associated with traumatic events, such as post-traumatic stress disorder (PTSD), may be prone to malingering due to the subjective nature of trauma symptomology. In general, symptoms tend to be inflated when an external reward (i.e., compensation) is associated with the claim. The present study was designed to test whether malingered claims of PTSD symptoms differed as a function of the type of trauma being malingered (accident, disaster, sexual assault) and the motivation for malingeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 67 publications
(103 reference statements)
5
33
0
Order By: Relevance
“…Second, the results of the pilot study replicated previous findings that suggested a subtle difference between malingerers instructed with a civil case vignette and those instructed with a criminal case vignette (Merckelbach et al, 2009;Peace & Masliuk, 2011). Note, however, that study 2 did not find differences between the civil and criminal malinger groups in MSVT and SIMS failure rates.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Second, the results of the pilot study replicated previous findings that suggested a subtle difference between malingerers instructed with a civil case vignette and those instructed with a criminal case vignette (Merckelbach et al, 2009;Peace & Masliuk, 2011). Note, however, that study 2 did not find differences between the civil and criminal malinger groups in MSVT and SIMS failure rates.…”
Section: Discussionsupporting
confidence: 78%
“…One explanation for this discrepancy might be that study 2 relied on case vignettes that were highly similar in content (i.e., both centred on a person witnessing a close family member in danger) and that both malinger groups were instructed to feign psychological symptoms. The most systematic simulation study to date that addressed this issue is that of Peace and Masliuk (2011). These authors determined that feigning motivated by revenge or compensation resulted in higher symptom levels than feigning motivated by a need for attention.…”
Section: Discussionmentioning
confidence: 99%
“…Feigners, besides the financial incentive, were asked to imagine having a chance to revenge to the train company. Revenge was shown to be a strong motivator (Peace & Masliuk, 2011). Yet, in reality, people claiming PTSD are often confronted with a significantly stronger (financial or emotional) incentive (positive or negative), which can have a different influence on their response style (Peace & Masliuk, 2011;Peace & Richards, 2014;Resnick et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, most research focusses on the development of symptom scales that test for over-reporting and exaggerated complaints known as the Symptom Validity Tests (SVTs). The 'over-the-top' way of responding to symptoms inventories was shown to be a trademark of fabricated PTSD reports (e.g., Hall & Hall, 2007;Peace & Masliuk, 2011;Tracy & Rix, 2017). Thus, the idea behind the SVTs is that those who fabricate their symptoms will overendorse items on symptom inventories, even if they contain bizarre/implausible complaints (Merckelbach & Smith, 2003).…”
Section: Symptom Endorsement In Feigned Ptsdmentioning
confidence: 99%
“…Furthermore, Peace and Masliuk (2011) found in their experimental study indications that fantasy proneness is related to a stronger symptom over-reporting tendency.…”
Section: The Brand Et Al Articles Provide Problematic Simplificationsmentioning
confidence: 93%